2010
DOI: 10.5688/aj7406110
|View full text |Cite
|
Sign up to set email alerts
|

Professional Competencies Learned Through Working on a Medication Education Project

Abstract: Objectives. To implement a medication education project and assess the competencies students learned and implemented in professional practice after graduation. Design. Fourth-year pharmacy students planned, carried out, and reported on a real-life project during 1 study year. Outside experts and 2 faculty members facilitated the work. The aim of the medication education project was to create material that schoolteachers could use to teach children about rational use of medicines. Assessment. All students who h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
0
9
0
1
Order By: Relevance
“…[20][21][22] A similar effort toward increased education in Social Pharmacy is evident in both developed and developing countries. [23][24][25] The respondents in our survey admitted the importance of Social Pharmacy and confirm changes in their curriculum in the near future in this field.…”
Section: Discussionmentioning
confidence: 64%
“…[20][21][22] A similar effort toward increased education in Social Pharmacy is evident in both developed and developing countries. [23][24][25] The respondents in our survey admitted the importance of Social Pharmacy and confirm changes in their curriculum in the near future in this field.…”
Section: Discussionmentioning
confidence: 64%
“…As such, teamwork and interactions with their peers seem to be important elements that structure the student learning experience. This is an analysis that fits with the one made by Hämeen-Anttila et al, (2010) which showed that after obtaining a pharmacy diploma, the skills that students declare having acquired were teamwork and social interaction skills. A course like the one offered at the Université de Montréal, combining team-based learning and project-based learning seems to contribute to this.…”
Section: E3-271: For the 360 Degree Assessment I Find That It Is Alsmentioning
confidence: 83%
“…In recent years, increasing incidence of chronic diseases, challenges of budget constraints, and increased morbidity and mortality associated with medicine use have led health systems to require professionals to develop skills such as patient-centered care and multidisciplinary teamwork. 1 -4 This scenario calls for a pharmaceutical service model that goes beyond access to medicines and includes the provision of clinical services 5 with a view to achieving satisfactory health outcomes, thus requiring changes in the teaching and practice of the pharmaceutical profession. 3…”
Section: Introductionmentioning
confidence: 99%
“…1 -4 This scenario calls for a pharmaceutical service model that goes beyond access to medicines and includes the provision of clinical services 5 with a view to achieving satisfactory health outcomes, thus requiring changes in the teaching and practice of the pharmaceutical profession. 3…”
Section: Introductionmentioning
confidence: 99%